The Interfaith Nyadran Tradition as a Manhaj of Islam Nusantara Da’wah in the Perspective of Multiculturalism - Muhyiddin, Ahmad Shofi; Musahadi, Musahadi; Sulthon, Muhammad (ADDIN, 2023)
The development of a humanist da’wah model in the midst of multiculturalism can be realized through the interfaith nyadran tradition. The aim of this research is to develop a pioneering model of cultural and multicultural da’wah, with a case study on the interfaith nyadran tradition as a manhaj of Islam Nusantara Da’wah. The author uses an ethnographic-qualitative method in searching and presenting interfaith nyadran tradition data which is then analyzed with a philosophical hermeneutic approach to find manhaj of Islam Nusantara da’wah from a multiculturalism perspective. The results of this study found several findings: First, the interfaith nyadran tradition of Genting village, Jambu district, Semarang Regency is full of multicultural values, including: the value of unity in diversity, the value of respecting and accepting differences in religious, social and cultural backgrounds, even organizational groups, values prioritizing togetherness in harmony, the value of equality in the absence of discrimination of the majority over minorities, the value of social justice, the value of good prejudice in social interaction and the value of fighting for human rights. Second, the values of multiculturalism in the interfaith nyadran tradition then become an approach strategy (manhaj) in da’wah based on Islamic dialectics and local cultural traditions that are unique to the archipelago. Third, Islam Nusantara da’wah has several characteristics, namely: da’wah that continuously engages in dialectics with local culture, da’wah that cares for the spirit of multiculturalism, da’wah that avoids religious extremism, and da’wa that fights for human rights. Finally, the interfaith nyadran tradition in the scientific structure of Islam Nusantara da’wah in the perspective of multiculturalism is included in the category of approach strategy (manhaj) based on human creativity (al-manāhij al-basyariyyah), which includes: manhaj ṡaqāfiyyah (cultural approach), al-manhaj al-'āṭifi (feeling approach) and manhaj jamā'iyyah (group approach).